Questions of travel : postmodern discourses of displacement - Kaplan, Caren (Post-contemporary interventions, 1996)
Contemporary theory is replete with metaphors of travel-displacement, diaspora, borders, exile, migration, nomadism, homelessness, and tourism to name a few. In Questions of Travel, Caren Kaplan explores the various metaphoric uses of travel and displacement in literary and feminist theory, traces the political implications of this "traveling theory," and shows how various discourses of displacement link, rather than separate, modernism and postmodernism.\Addressing a wide range of writers, including Paul Fussell, Edward Said, James Clifford, Gilles Deleuze, Jean Baudrillard, Gayatri Spivak, Edward Soja, Doreen Massey, Chandra Mohanty, and Adrienne Rich, Kaplan demonstrates that symbols and metaphors of travel are used in ways that obscure key differences of power between nationalities, classes, races, and genders. Neither rejecting nor dismissing the powerful testimony of individual experiences of modern exile or displacement, Kaplan asks how mystified metaphors of travel might be avoided. With a focus on theory's colonial discourses, she reveals how these metaphors continue to operate in the seemingly liberatory critical zones of poststructuralism and feminist theory. The book concludes with a critique of the politics of location as a form of essentialist identity politics and calls for new feminist geographies of place and displacement.\An important and timely intervention into contemporary theoretical debates, Questions of Travel will be of interest to scholars in a wide variety of disciplines, including literary criticism, cultural studies, feminist theory, colonial and postcolonial studies, geography, anthropology, and sociology.